Jaringan Syaraf Tiruan Dalam Menganalisa Bentuk Sel Darah Putih Dengan Menggunakan Metode Radial Basis Function (RBF) - Yuyung Aquen Nababan (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
White blood cells are cells that form components in the blood. White blood cells have a life span of between six to eight days. Analyzing white blood cells is still carried out through a series of laboratory tests which can take a while. This test covers the shape of the morphology of blood cells, which until now is generally still done manually. This manual inspection certainly has a low level of accuracy and accuracy because it is carried out humanely and has a possible degree of difference in analysis. This causes a lack of accuracy and accuracy performed by doctors and health laboratory personnel because the physical condition, knowledge, accuracy and concentration of doctors and health laboratory personnel can influence the identification of diseases so that there may be differences in analysis between one doctor and another. On hematology examination can be overcome manually by creating an automatic system with the help of a computer. Therefore, in this study the author tries to provide alternative solutions to the problem with the Radial Basis Function learning method, which according to his theory will produce higher accuracy values and faster iteration times